Pelatihan Pembuatan Wadah Air dan Penyaring Air melalui Diversifkasi Bahan Alam sebagai Solusi Air Bersih dan Udara Bersih - Zuhro, Siti Fatimatul; Sartono, Sartono; Sapriyadi, Sapriyadi; Rinarso, Berlian Dwi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Banten Province faces a significant clean water challenge, impacting coastal businesses like the Sinar Mutiara SME. In response, a community service program was launched to empower residents by teaching them to build natural water filters from local materials, aiming to improve water access, productivity, and environmental awareness. Problem: The SME's production was hampered by three key issues: limited clean water due to brackish sources, local air pollution from waste and nearby projects, and a lack of knowledge in using natural resources for solutions. Method: Adopting a participatory method, the program began with a needs survey and selected effective local plants like water hyacinth and betel leaf. The community received hands-on training through workshops, followed by the implementation and evaluation of pilot models. Results: The initiative was highly successful in improving the murky and brackish water. The training was so effective that 15 families independently replicated the purification system. Evaluations from 20 participants were overwhelmingly positive. Conclusion: In conclusion, educating communities on using plants for water purification proved to be a practical, affordable, and empowering solution for the Tangerang coastal region, significantly improving water quality and providing residents with relevant skills.